THE DEVELOPMENT TREND OF INTERNATIONAL EDUCATION IN CHINA AND THAILAND - Zhao, shaoyuan; Sirathanakul, Kumron (วารสาร มจร พุทธปัญญาปริทรรศน์, 2025)
The concept of international education has gained significant attention in recent years as the world becomes more interconnected and globalized. China and Thailand have both made significant investments in their education systems, including a focus on internationalizing their education systems. This dissertation aims to explore the development trends of international education in China and Thailand, with a focus on the drivers, challenges, and strategies for developing international education in both countries. The study is based on a literature review of research studies, reports, and data on international education in both countries, as well as interviews with experts, policymakers, and practitioners in the field of international education. The findings of this study provide insights into the current state and future trends of international education in China and Thailand, and highlight the importance of comprehensive policies and effective strategies to overcome the challenges facing international education in both countries. In conclusion, this research provides a comprehensive comparative analysis of the development trends of international education in China and Thailand, shedding light on the similarities and differences in their international education landscape and offering valuable insights for policymakers, educators, and researchers. The findings have important theoretical and practical implications, as well as providing direction for future research and policy development in international education.